KONSELING BEHAVIORISTIK TEKNIK SELF-MANAGEMENT DALAM MENGATASI RENDAHNYA ETIKA PERGAULAN SIKAP SOPAN SANTUN SISWA - Rahayu, Yuni; Masturi, Masturi; Kiswantoro, Arista (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The aims of this research are 1. To describe the factors that cause the low level of politeness among students in the social etiquette of class VIII SMPN 4 Kudus. 2. Overcoming the social ethics of student courtesy through behavioral counseling services with self-management techniques for class VIII SMPN 4 Kudus. This type of research is a qualitative research in the form of a case study conducted at SMPN 4 Kudus. The subjects of this study were two class VIII students who had problems with social ethics and politeness. Data collection techniques include observation, interviews, documentation. The results showed that by providing behavioristic counseling services with self-management techniques. The counselee is able to change problematic behavior into expected behavior, namely being polite, being able to respect and respecting parents, being friendly in the school environment, being able to respect the opinions and decisions of others